Calpain-6 controls the fate of sarcoma stem cells by promoting autophagy and preventing senescence - Andrique, Caroline; Morardet, Laetitia; Linares, Laetitia K.; Cissé, Madi Y.; Merle, Candice; Chibon, Frédéric; Provot, Sylvain; Haÿ, Eric; Ea, Hang-Korng; Cohen-Solal, Martine; Modrowski, Dominique (JCI insight, 2018)
Sarcomas are still unsolved therapeutic challenges. Cancer stem cells are believed to contribute to sarcoma development, but lack of specific markers prevents their characterization and targeting. Here, we show that calpain-6 expression is associated with cancer stem cell features. In mouse models of bone sarcoma, calpain-6-expressing cells have unique tumor-initiating and metastatic capacities. Calpain-6 levels are especially high in tumors that have been successfully propagated in mouse to establish patient-derived xenografts. We found that calpain-6 levels are increased by hypoxia in vitro and calpain-6 is detected within hypoxic areas in tumors. Furthermore, calpain-6 expression depends on the stem cell transcription network that involves Oct4, Nanog, and Sox2 and is activated by hypoxia. Calpain-6 knockdown blocks tumor development in mouse and induces depletion of the cancer stem cell population. Data from transcriptomic analyses reveal that calpain-6 expression in sarcomas inversely correlates with senescence markers. Calpain-6 knockdown suppresses hypoxia-dependent prevention of senescence entry and also promotion of autophagic flux. Together, our results demonstrate that calpain-6 identifies sarcoma cells with stem-like properties and is a mediator of hypoxia to prevent senescence, promote autophagy, and maintain the tumor-initiating cell population. These findings open what we believe is a novel therapeutic avenue for targeting sarcoma stem cells.